THE GENUS PITYRANTHE Thw. (Tiliaceae). - A.J.G.H KOSTERMANS (Reinwardtia, 1961)
1. Pityranthe Thw. is incorporated in Diplodiscus Turcz. 2. A discussion on the characters of both genera is presented, together with a note, concerning priority. 3. An emendated description of Diplodiscus verrucosus (Thw.) Kosterm., comb. nov. is presented.